BUILDING MODERATE AND NATIONALLY MINDED: HOW ISLAMIC MODERATION AND NATIONAL EDUCATION ARE CULTIVATED IN A TAREKAT-BASED PESANTREN - Adi Wibowo; Khoirun Nisa (PEDAGOGIK : JURNAL PENDIDIKAN, 2025)
This study examines the concepts of Islamic moderation and national education in the educational thought and practice. This research is based on concerns about religious radicalism and the weakening of national commitment among the younger generation in Indonesia, which demands an educational model that integrates religious values with civic responsibility. Using a qualitative case study design, this study analyzes data collected through observation, interviews, documentation, and lecture materials, which are then reduced, triangulated, and critically interpreted in relation to relevant theoretical frameworks. The findings indicate that Islamic moderation is implemented through nationalist da'wah, political ijtihad based on national commitment, and character education in Islamic boarding schools (pesantren). This confirms that Islamic boarding schools are effective in cultivating moderate Islamic values while strengthening national consciousness. This study contributes to the growing body of scholarship on Islamic moderation by demonstrating that traditional Islamic boarding schools and local ulama can play a crucial role in fostering inclusive religiosity, social cohesion, and resistance to radical ideologies in contemporary Indonesia.